Implementation of the Independent Campus Learning Program Health Study Program Curriculum - Siska Septiana, Krisna; Ari Indra Susanti; Hadi Susiarno; Nurfitriyani, Ela (JTP - Jurnal Teknologi Pendidikan, 2024)
Education serves as a transformative process that enhances human potential for the betterment. The Minister of Education and Culture initiated the Independent Learning-Independent Campus Program (MBKM) in 2020 to equip graduates with the skills to meet global challenges. However, since its inception at universities, the health study program curriculum has struggled to align with this policy. This study investigates the MBKM's implementation within the health study program curriculum. A literature review was conducted, sourcing material from databases such as PubMed, Science Direct, Google Scholar, and Worldcat, focusing on literature published from 2020 to 2024 in both Indonesian and English with full-text availability. The literature review aimed to provide a thorough understanding of the subject, with inclusion and exclusion criteria ensuring the relevance and integrity of the literature. The findings reveal that several health study programs have adopted the Independent Learning-Independent Campus Program, noting improvements in students' hard and soft skills in preparation for employment. Nonetheless, challenges persist in the Independent Learning-Independent Campus Program execution, including inadequate preparedness for learning, lecturer/facilitator involvement, and a need for more detailed information on MBKM Campus Program's implementation.